Prevalence of motile Aeromonads in chicken meat and their growth during refrigeration storage - Abdul Aziz, Saleha; N. Thiruvengadam, Vanitha (Veterinary Association Malaysia, 2003)
The presence of motile aeromonads in chicken meat from the local wet markets was studied. The finding showed that 83.3% of the meat was positive for motile Aeromonas. The most frequently isolated species was Aeromonas sobria (57.0%), followed by A. hydrophila (23.0%) and A. caviae (20.0%). The Aeromonas sp. count at time of purchase which was in the range of 13 x 102 /g to 23 x 103/g, was found to increase about 10 to 100- fold after seven days of refrigeration at 5°C.